2013
DOI: 10.1016/j.chom.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Infection and Immunity

Abstract: Iron is an essential nutrient for both humans and pathogenic microbes. Because of its ability to exist in one of two oxidation states, iron is an ideal redox catalyst for diverse cellular processes including respiration and DNA replication. However, the redox potential of iron also contributes to its toxicity, thus iron concentration and distribution must be carefully controlled. Given the absolute requirement for iron by virtually all human pathogens, an important facet of the innate immune system is to limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
1,011
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,028 publications
(1,045 citation statements)
references
References 90 publications
13
1,011
0
21
Order By: Relevance
“…This finding also speculated that dietary inclusion of MCF‐MORS would cause noticeable immune phagocytic actions and inflammatory defenses than UF‐MOS, suggesting its potent usefulness in clinical and signaling hematologic wellness (Burchi, Fanzo, & Frison, 2011; Vikash, Suvra, Debtanu, Lokesh, & Kundan, 2013). This observation corroborated the recent finding which reported that diets containing no or little anti‐nutrients such as oxalates, saponins, tannins, phytates, and lectins with tolerable proportions of essential minerals possess a greater potential to fight infections (James & Eric, 2013) and promote the immune cells against pathogens, damaged cells, cancerous cells, and abnormal stem cell development (Friedenberg et al., 2016; Kaustav et al., 2016). However, we proposed that MO seeds fermented by fungus known as R. stolonifer reduced possible risk of immune suppression and leukemia than nonfermented.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This finding also speculated that dietary inclusion of MCF‐MORS would cause noticeable immune phagocytic actions and inflammatory defenses than UF‐MOS, suggesting its potent usefulness in clinical and signaling hematologic wellness (Burchi, Fanzo, & Frison, 2011; Vikash, Suvra, Debtanu, Lokesh, & Kundan, 2013). This observation corroborated the recent finding which reported that diets containing no or little anti‐nutrients such as oxalates, saponins, tannins, phytates, and lectins with tolerable proportions of essential minerals possess a greater potential to fight infections (James & Eric, 2013) and promote the immune cells against pathogens, damaged cells, cancerous cells, and abnormal stem cell development (Friedenberg et al., 2016; Kaustav et al., 2016). However, we proposed that MO seeds fermented by fungus known as R. stolonifer reduced possible risk of immune suppression and leukemia than nonfermented.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the reduction in the levels of RBC and Hb at higher doses may be linked to the remarkable dietary depletion of Mn 2+ and Zn 2+ levels by MCF‐MORS. Study has shown that Mn 2+ and Zn 2+ could be incorporated in human diets if RBC and Hb are depleted and they are also redox‐active elements essential as catalytically active cofactors in enzymes and structurally stabilizing protein production as well as enhancing immune systems (Friedenberg et al., 2016; James & Eric, 2013). Additionally, animal fed with 7.5%, 15%, 22.5%, and 30% MCF‐MORS showed no significant ( p  <   0.05) difference in WBC count in relation to the control (Figure 4), whereas animals fed with UF‐MOS were significantly ( p  <   0.05) reduced the level of WBC when compared to corresponding control (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Our studies reveal two faces of host Cu during infection with C. albicans: while serum Cu elevates, Cu can become limiting at the major site of infection in the kidney. As one possibility, the host may intentionally restrict Cu as part of an innate nutritional immunity response, similar to host withholding of Fe, Mn, and Zn for invading microbes (3)(4)(5)(6)(7)(8)(9)(10). Recent studies by Brown and colleagues have shown that during C. albicans infection of the kidney, Fe moves away from sites of fungal lesions in the cortex to the medulla as an apparent mechanism for Fe withholding (9).…”
Section: Resultsmentioning
confidence: 99%
“…As other pathogens, C. albicans relies on its host for micronutrients, such as metals, and the bioavailability of metals can greatly vary at the host-pathogen interface. As part of the innate immune response, the host deliberately withholds metals, such as Fe, Zn, and Mn, from invading microbes in a process known as "nutritional immunity" (3)(4)(5). Like other infectious agents, C. albicans is equipped to handle restrictions placed on these micronutrients and can activate diverse pathways for scavenging host sources of Fe and Zn (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The requirement for iron has created an ongoing struggle between hosts and pathogens as they vie for control of this nutrient. While free iron is already stringently limited in the bloodstream of mammalian hosts, bacterial infection triggers an innate immune response that sequesters iron even further, serving as a mechanism of limiting microbial proliferation (1). Invasive microorganisms, in turn, synthesize and excrete siderophores, soluble extracellular molecules that tightly bind and help solubilize iron found in the environment.…”
mentioning
confidence: 99%